An SEM Analysis of the Competence to Reduce Transaction Costs of Export Management Companies in Thailand - Suwannarat, Pornlapas; Khantong, Sommai; Jantarajaturapath, Napat (วารสารการบัญชีและการจัดการ, 2019)